PPARγ coactivator-1α expression during thyroid hormone- and contractile activity-induced mitochondrial adaptations - Irrcher, Isabella; Adhihetty, Peter J.; Sheehan, Treacey; Joseph, Anna-Maria; Hood, David A. (American Journal of Physiology: Cell Physiology, 2003)
The transcriptional coactivator the peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) has been identified as an important mediator of mitochondrial biogenesis based on its ability to interact with transcription factors that activate nuclear genes encoding mitochondrial proteins. The induction of PGC-1α protein expression under conditions that provoke mitochondrial biogenesis, such as contractile activity or thyroid hormone (T 3 ) treatment, is not fully characterized. Thus we related PGC-1α protein expression to cytochrome c oxidase (COX) activity in 1) tissues of varying oxidative capacities, 2) tissues from animals treated with T 3 , and 3) skeletal muscle subject to contractile activity both in cell culture and in vivo. Our results demonstrate a strong positive correlation ( r = 0.74; P < 0.05) between changes in PGC-1α and COX activity, used as an index of mitochondrial adaptations. The highest constitutive levels of PGC-1α were found in the heart, whereas the lowest were measured in fast-twitch white muscle and liver. T 3 increased PGC-1α content similarly in both fast- and slow-twitch muscle, as well as in the liver, but not in heart. T 3 also induced early (6 h) increases in AMP-activated protein kinase (AMPKα) activity, as well as later (5 day) increases in p38 MAP kinase activity in slow-twitch, but not in fast-twitch, muscle. Contractile activity provoked early increases in PGC-1α, coincident with increases in mitochondrial transcription factor A (Tfam), and nuclear respiratory factor-1 (NRF-1) protein expression, suggesting that PGC-1α is physiologically important in coordinating the expression of the nuclear and mitochondrial genomes. Ca 2+ ionophore treatment of muscle cells led to an approximately threefold increase in PGC-1α protein, and contractile activity induced rapid and marked increases in both p38 MAP kinase and AMPKα activities. 5-Aminoimidazole-4-carboxamide-1-β-d-ribofuranoside (AICAR) treatment of muscle cells also led to parallel increases in AMPKα activity and PGC-1α protein levels. These data are consistent with observations that indicate that increases in PGC-1α protein are affected by Ca 2+ signaling mechanisms, AMPKα activity, as well as posttranslational phosphorylation events that increase PGC-1α protein stability. Our data support a role for PGC-1α in the physiological regulation of mitochondrial content in a variety of tissues and suggest that increases in PGC-1α expression form part of a unifying pathway that promotes both T 3 - and contractile activity-induced mitochondrial adaptations.